MENJELAJAHI PENGALAMAN PEMAIN DALAM GAME HOROR AMBIENT SUREALISME DENGAN METODE GDLC DAN EKSPERIMEN - Tony Wibowo; Joyce Joyce; Willson Andrew; Jefrry Arispratama; Angelina Rianti; Jimmy Pratama (SKANIKA: Sistem Komputer dan Teknik Informatika, 2026)
As the popularity of horror games continues to grow, understanding the role of atmospheric elements such as ambience and surrealism in shaping fear and players’ emotional engagement has become an important yet underexplored area of study. This research aims to examine the relationship between surrealism, ambience, and fear in horror games through an experimental case study set in an environment inspired by Southeast Asia. Using a qualitative approach, the study involved 128 participants who played a game developed by the researcher and participated in in-depth interviews to explore their emotional experiences. Findings from the 128 participants indicate that audio elements are the most dominant factor in eliciting fear, particularly sounds such as creaking doors, environmental noises, silence, and dripping water. Visual elements, including dim lighting, narrow corridors, and decaying environments, serve as supporting components that enhance the surreal and immersive atmosphere. These findings suggest that effective horror is more strongly constructed through subtle ambience and psychological cues rather than explicit visual threats, demonstrating that audio- and psychologically driven design approaches effectively enhance player immersion and emotional engagement.